Interfacial Rashba band splitting in the organohalide lead perovskites: an ab-initio study. (7th June 2021) - Shalmashi, Kazhal; Khosravi, Heidar; Boochani, Arash; Azar, Yavar T.
Abstract: Halide perovskites have attracted significant attention in the past few years due to the spectacular growth in the efficiency of perovskite-based devices. The charge transfer at the metal oxide/perovskite interface is one of the most crucial device operational mechanisms. Understanding the interface features and their impact on device efficiency is becoming increasingly important. The built-in interfacial potential governs the charge transfer direction and rate. Concurrently, a spin–orbit coupling joint to the local electric field at the interface can cause a Rashba–Dresselhaus band splitting. Here, the geometrical and electronic structure of the interface between different terminated perovskite layers and titania is explored employing ab-initio techniques. The obtained results reveal higher stability and more beneficial band alignment for the PbI-terminated perovskite/titania interface. By estimating the electric field at the interface, the model slab perovskite response to the external field has been studied systematically. Rashba coefficients have been calculated for both conduction and valence bands. These results indicate a tunable band splitting at the presence of an external field or structural symmetry breaking. Our findings could help to understand the interfacial effects and further develop spin-based devices through Rashba-like effects.